Efektifitas Perputaran Persediaan Dan Perputaran Piutang Dalam Meningkatkan Profitabilitas Pada PT Indo Kordsa Tbk - Devi Dwi Nilasari; Nuryadi Nuryadi (Jurnal Riset Akuntansi, 2023)
This research aims to determine inventory turnover and accounts receivable turnover in increasing profitability at PT Indo Kordsa Tbk. The data studied is in the form of the financial statements of PT Indo Kordsa Tbk for 2018-2021. The data collection technique used is the documentation technique. The data analysis technique in this study is a qualitative descriptive analysis technique. The results of this study state that 1) inventory turnover that has been carried out by the company for 4 years has not been effective 2) receivable turnover that has been carried out by the company for 4 years has not been effective 3) profitability is considered less than optimal because the level of sales has decreased resulting in inventory turnover and receivable turnover not yet effective so that it has not been able to help obtain maximum profitability.